Estrogen and progesterone receptors in breast cancer– the current state of knowledge - Piekarski, Janusz (Contemporary Oncology/Współczesna Onkologia, 2005)
The expression of estrogen and progesterone receptors provides strong and useful predictive factors. As the response to hormonal treatment is closely related to the content of estrogen and progesterone receptors in breast cancer, an assessment of the expression of these receptors allows us to predict the response of the cancer cells to hormonal treatment. The expression of estrogen and progesterone receptors is a weak prognostic factor. Statistically significant, positive prognostic effects of estrogen and progesterone receptor expression can only be shown in studies with large numbers of cases. In small or medium scale studies, the prognostic influence of the expression of estrogen and progesterone receptors is weak or absent. For almost four decades, the action of estrogens was attributed to one receptor. However, in 1996, a new estrogen receptor, estrogen receptor beta, was discovered. The first, well known and well characterized receptor, described five decades ago, was defined as estrogen receptor alpha. Estrogen receptor beta is encoded by a different gene to estrogen receptor alpha. The progesterone receptor also has two isoforms: A and B. Both progesterone receptors are encoded by the same gene, but different promoters are used for its transcription. The structure of both proteins is very similar. Nowadays, three methods are used for the assessment of the expression of steroid receptor content in breast cancers: the Ligand Binding Assay (LBA), Enzyme Immuno Assay (EIA) and Immuno Histo/Cytochemical Assay (IHA/ICA). The results of assessments performed with the use of these methods are similar.